2017
DOI: 10.3390/mi8040124
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Microfluidics in Cytotoxicity and Nanotoxicity Experiments

Abstract: Many unique chemical compounds and nanomaterials are being developed, and each one requires a considerable range of in vitro and/or in vivo toxicity screening in order to evaluate their safety. The current methodology of in vitro toxicological screening on cells is based on well-plate assays that require time-consuming manual handling or expensive automation to gather enough meaningful toxicology data. Cost reduction; access to faster, more comprehensive toxicity data; and a robust platform capable of quantita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 69 publications
0
11
0
Order By: Relevance
“…Microfluidics offer the ability to introduce many biological conditions in a single device and replicate in vivo situations and dimensions [67]. Therefore, it allows rapid, real-time, and multi-sample analysis, which creates a versatile, non-invasive technique that can produce quantitative information concerning alterations in cellular function upon exposure to different NMs [68,69].…”
Section: Fluidic-based Cell-on-chip (Coc)mentioning
confidence: 99%
“…Microfluidics offer the ability to introduce many biological conditions in a single device and replicate in vivo situations and dimensions [67]. Therefore, it allows rapid, real-time, and multi-sample analysis, which creates a versatile, non-invasive technique that can produce quantitative information concerning alterations in cellular function upon exposure to different NMs [68,69].…”
Section: Fluidic-based Cell-on-chip (Coc)mentioning
confidence: 99%
“…They generate a gradient in the composition of a solution, like, in this case, the toxic compound to be tested. Thanks to this PDMS gradient generating devices, several works have demonstrated that High-Throughput (HTP) toxicity analysis of specific compounds can be simultaneously carried out, at different concentrations, on chip, for cytotoxicity assessment (Hosokawa et al, 2011;McCormick et al, 2017;Li et al, 2018) PDMS has been the most commonly used material for the fabrication of prototypes during the last decade but it presents some drawbacks such as absortion of small molecules and high gas permeability, thus there is a demand to fabricate microfluidic devices made of other polymers. As an example, Nguyen et al reported a hybrid polymeric microfluidic device for cytotoxicity testing, made of poly(methyl methacrylate) with integrated polyethylene terephthalate (Nguyen et al, 2019).…”
Section: Sotf-lithographymentioning
confidence: 99%
“…30,34 For these reasons, several microfluidic devices mimicking in vivo environments have been designed and utilised for toxicity screening. 35–38 These devices allow monitoring of the interaction between nanoparticles and cells exposed to mechanical stress (fluidic shear stress and cyclic stretching) or cultured within the 3D matrix space.…”
Section: Introductionmentioning
confidence: 99%